Analisis Pengaruh Ulasan Pelanggan terhadap Peningkatan Penjualan Produk pada Platform E-Commerce Shopee - Irawan, Abit; Damayanti, Damayanti (TIN: Terapan Informatika Nusantara, 2025)
This study aims to analyze the influence of customer reviews on increasing product sales on the Shopee e-commerce platform. The background of this research is based on the rapid growth of internet users and online shopping trends in Indonesia, which have driven the expansion of digital commerce activities. This research employs a quantitative approach using survey and literature study methods. The study was conducted in Bandar Lampung City with 50 respondents who are active Shopee users that have made purchases, read, and provided product reviews within the last three months. Although the number of respondents is relatively limited and covers only one region, the findings still provide an initial overview of consumer behavior on the Shopee platform. Primary data were collected through questionnaires using a Likert scale of 1–5, while secondary data were obtained from documentation and relevant literature. Data analysis was conducted using validity tests, normality tests, F-tests, and t-tests with the assistance of SPSS version 25 software. The results show that the customer review variable has a positive and significant influence (Sig. < 0.05) on product sales growth. The F-value of 65.591 and t-value of 7.175 indicate a strong relationship between customer reviews and consumer purchasing decisions. Therefore, it can be concluded that customer reviews are an important factor in building trust, enhancing product reputation, and increasing sales on the Shopee e-commerce platform, although the results of this study are still limited in terms of national generalization.